Attention and awareness: Representation of visuomotor space in split-brain patients. (January 2020) - Dosso, Jill A.; Chua, Romeo; Weeks, Daniel J.; Turk, David J.; Kingstone, Alan
Abstract: Each cerebral hemisphere primarily controls and receives sensory input with regard to the contralateral hand. In the disconnected brain (split-brain), when the hands are uncrossed, direct visual access to each hand is available to the controlling (contralateral) hemisphere. However, when a hand crosses the midline, visual and tactile information regarding the hand are presented to different hemispheres. It is unknown how a contralateral hemisphere codes the position and orientation of a visually inaccessible hand in the disconnected brain. The present work addresses this issue. We ask how each hemisphere represents "its" hand across hand positions that span the midline in the absence of cortical input from the contralateral hemisphere. In other words, when a hand is placed across the midline and is visually inaccessible, is it represented by the controlling hemisphere: (1) in accordance with its new position with respect to the body (e.g., a left hand "becomes" a right effector when it crosses the midline), (2) with left/right position information unaltered (e.g., the left hand is represented as "left" regardless of its location), or (3) stripped of its location information altogether? The relationship between hand position and the spatial codes assigned to potential responses (an index of hand representation) was investigated in two split-brain patients using direct (Experiment 1) and orthogonal (Experiment 2) S-R compatibility paradigms. S-R compatibility effects in split-brain patients were consistent with those displayed by typical individuals. These findings suggest that position-based compatibility effects do not rely on cross-cortical connections. Rather, each hemisphere can accurately represent the full visuomotor space, a process that appears to be subserved by subcortical connections between the hemispheres.